2016
DOI: 10.1016/j.amsu.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Are all after-hours diagnostic imaging appropriate? An Australian Emergency Department pilot study

Abstract: BackgroundThis study was aimed at determining the extent to which after-hours diagnostic imaging is appropriate within the case hospital's Emergency Department. This was amid growing concerns of the inappropriateness of some medical investigations within the Australian health-care system.MethodsAfter-hours referral data and patient notes were used in reviewing the clinical case. Diagnostic imaging was deemed appropriate if reflective of clinical guidelines, and if not reflective, whether the investigation chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Other studies reported similar reasons for inappropriate radiologic workup: medico-legal issues, [5] diagnostic uncertainty, [6] inadequate education and training, [7] requests from consulting subspecialty physicians, increased workloads within the ED, [8] and patient self-referral. [9] Contrary to our data, Gardiner and Zhai [10] reported just 0.8% of CXRs performed during off hours as inappropriate in a study from a teaching hospital in Australia.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies reported similar reasons for inappropriate radiologic workup: medico-legal issues, [5] diagnostic uncertainty, [6] inadequate education and training, [7] requests from consulting subspecialty physicians, increased workloads within the ED, [8] and patient self-referral. [9] Contrary to our data, Gardiner and Zhai [10] reported just 0.8% of CXRs performed during off hours as inappropriate in a study from a teaching hospital in Australia.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, a lower appropriateness rate compared with other hospital settings, such as the emergency department, was shown. 14 …”
Section: Discussionmentioning
confidence: 99%
“…26 studies rated 26,715 CTs [21, 23, 63-65, 67, 72-74, 76, 77, 81, 83, 86, 89, 92, 93, 98-104, 106, 107] with an overall appropriateness of 60% (n = 16,363/27,309). Eleven studies [20, 23, 62, 66, 83-85, 87-89, 104] reported an appropriateness of 55% in 7729 reviewed radiographs (n = 4271/7729) and two studies [88,104] reviewed 1535 radiological ultrasounds with an overall appropriateness of 44% (n = 680/1535). Overall, there are no patterns regarding size of study population and appropriateness (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reviewed [74,81,100]. The appropriateness of head/neck CT in adults/ patients of unknown age was rated with national guidelines [21,63,72,104], EU guidelines [100] or ACR AC [93,101]. It varied between 44% (n = 26/59) [63] and 98% (n = 63/64) [104], averaging out at an overall appropriateness of 79% (n = 532/675).…”
Section: Resultsmentioning
confidence: 99%